The Effect of Social Media Campaign Adoption: Content and Message Quality to Brand Image as a Competitive Advantage - Revita Desi Hertin; Hadi Wijaya; Alfi Maghfuriyah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The development of the digital world encourages business actors to innovate in the process of introducing brands to the public. Brand image greatly influences how consumers view a product, this also greatly influences the decision to purchase a product. This brand introduction process is carried out using several methods including using social media marketing. Several factors influence the process of introducing this brand, the use of the wrong message and the use of poor-quality content will affect the results. This study aims to analyze the Influence of Content Quality and Message Quality on Brand Image Brand in MSMEs in Tirtajaya Village. With a total of 50 respondents from MSME actors, data was collected using a questionnaire which made this research method Quantitative. Based on data analysis, it was found that Content Quality and Message Quality had a positive effect on how the public views the brand. Further research can be improved by measuring other variables such as the selection of marketing media.